Preparation and magnetic properties of nitroxide radical liquid crystalline physical gels. (13th April 2017) - Takemoto, Yusa; Uchida, Yoshiaki; Shimono, Satoshi; Yamauchi, Jun; Tamura, Rui
ABSTRACT: Liquid crystalline physical gels which consist of a chiral racemic nitroxide radical compound (±)-1 showing a nematic phase and a diamagnetic, chiral organic gelator ( R, R )-2 were prepared to investigate the effects of the gelator on the "positive magneto-LC effects" observed in the nematic phase of (±)-1 and the molecular alignment of (±)-1 in the resulting nematic gels. With the increasing amount of the gelator which decreased the domain size, the molecular reorientation by a magnetic field (0.34 T) was considerably restricted in the nematic gel phase and the intermolecular magnetic interactions (positive magneto-LC effects) increased in the fine and random nematic polydomain structure formed by self-assembled fibers of organic gelator molecules.